A Study of Post Covid Impact on the Foreign Trade of Ayurvedic & Herbal Products from India (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Objective- The objective of this chapter is to study the post covid-19 impact on growth of the ‘Indian Foreign Trade’ of ‘Ayurvedic’ products. This paper highlights the significant developments in ‘Ayurvedic’ business especially post pandemic and the influence of Covid-19 in ‘Indian Foreign Trade of ‘Ayurvedic’ products.Methodology- The paper employs exploratory research design considering the secondary data collected from various sources specifically the ‘Google’ content. The collected data has been edited and synthesized for fulfilling the objectives of the study.Findings- Analysis revealed that the Indian ‘Ayurvedic’, after the Covid-19 has been in a inflated demand and there has been a prediction of positive trend and enormous growth in the same as far as its foreign trade is concerned.Practical Implication- Being role and the contribution of ‘Ayurvedic’ products are increasing day by day domestically and globally, therefore this study is practically viable and especially the post covid-19 period.Originality/Value- Though the study is completely based on secondary data but the content analysis and synthesis aspect is the original work of an author. It adds value to the further studies in the same domain.